Mucus-secreting 'signet-ring' cells in CSF revealing the site of primary cancer. Issue 662 (December 1980) - Agnelli, G.; Gresele, P.
Abstract : A case is reported of leptomeningeal carcinomatosis in which identification of mucus-secreting 'signet-ring' carcinoma cells in the CSF allowed diagnosis of an otherwise asymptomatic gastric cancer. When lumbar puncture is performed, careful cytological examination of the CSF should be carried out in any undiagnosed patient with neurological symptoms and signs.